SwissFEL Aramis beamline photon diagnostics. (12th June 2018) - Juranić, Pavle; Rehanek, Jens; Arrell, Christopher A.; Pradervand, Claude; Ischebeck, Rasmus; Erny, Christian; Heimgartner, Peter; Gorgisyan, Ishkhan; Thominet, Vincent; Tiedtke, Kai; Sorokin, Andrey; Follath, Rolf; et al.
Abstract : The photon diagnostics available at the SwissFEL Aramis beamline are described. The working principles of various devices, their function and their expected or measured performance are discussed. Abstract : The SwissFEL Aramis beamline, covering the photon energies between 1.77 keV and 12.7 keV, features a suite of online photon diagnostics tools to help both users and FEL operators in analysing data and optimizing experimental and beamline performance. Scientists will be able to obtain information about the flux, spectrum, position, pulse length, and arrival time jitter versus the experimental laser for every photon pulse, with further information about beam shape and size available through the use of destructive screens. This manuscript is an overview of the diagnostics tools available at SwissFEL and presents their design, working principles and capabilities. It also features new developments like the first implementation of a THz‐streaking based temporal diagnostics for a hard X‐ray FEL, capable of measuring pulse lengths to 5 fs r.m.s. or better.